Understanding Police Misconduct Correlates: Does Gender Matter in Predicting Career-Ending Misconduct? - Gaub, Janne E. (Women & criminal justice, 2020)
Decades of research on police misconduct have produced mixed findings related to risk and protective factors. Although misconduct is a relatively rare and predominantly male phenomenon, demographic characteristics such as sex could provide context to better understand the influence of these factors in predicting misconduct. Using a large sample (N = 3,085) of matched police officers in the New York Police Department and a split-sample analysis testing equality of coefficients, this study identifies how common predictors of police misconduct operate differently for men and women.